Nano-optical imaging of van der Waals crystals: from ultrafast exciton dynamics to anisotropic waveguide modes - Mooshammer, Fabian; Xu, X.; Trovatello, C.; Shao, Y.; Zhang, S.; Schuck, P. J.; Basov, D. N. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
Near-field microscopy has emerged as a powerful tool for investigating the optoelectronic properties of van der Waals crystals on deeply subwavelength length scales. Complementary information may be obtained by interrogating the layered materials with electromagnetic radiation oscillating at vastly different frequencies: In the terahertz spectral range, for example, the polarizability of excitons in transition metal dichalcogenide (TMDC) heterostructures can be recorded on subcycle timescales - granting access to ultrafast formation dynamics or the exciton Mott transition with nanometer precision. In contrast, visible or near-infrared light propagates through thin van der Waals slabs in the form of waveguide modes (WMs). By resolving interference patterns in maps of the scattered electric field, the anisotropic dielectric tensor of layered materials is retrieved and signatures of strong light-matter coupling in the dispersion of the WMs are revealed. This approach also allows for boosting the potential of 3R-stacked TMDCs for applications in nonlinear optics by quantifying their birefringence, thus providing essential parameters for future phase-matched waveguide second harmonic generation and compact on-chip optical devices in general.
CRIS-Team Scopus Importer:2023-11-24
Keywords: anisotropy; exciton; near-field microscopy; near-infrared; terahertz; van der Waals; waveguide modes

Tracking the mid-infrared fine structure of quasi-1D excitons controlled by magnetic order - Liebich, M.; Florian, M.; Nilforoushan, N.; Mooshammer, F.; Mosina, K.; Sofer, Z.; Dirnberger, F.; Kira, M.; Huber, R.; Mooshammer, Fabian (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2024)
We use phase-locked few-cycle mid-infrared pulses to probe internal Rydberg-like transitions of quasi-one-dimensional excitons in the magnetic semiconductor CrSBr. The experimentally observed fine structure encompasses a lifted degeneracy of the 2p states induced by the anisotropic optoelectronic properties of the crystal. Furthermore, the Coulomb correlations are effectively controlled via the magnetic structure. By inducing a phase transition from antiferromagnetic to paramagnetic states either thermally or by applying an external magnetic field, we can switch excitons from strongly bound and mono-layer-localized to weakly bound and interlayer-delocalized species. A state-of-the-art many-body theory fully captures these findings and identifies the spin restrictions of the interlayer tunneling. In the paramagnetic phase, the reduced quantum confinement lowers the binding energy and increases the phase space for scattering. This in situ control of Coulomb correlations opens a path to shape phase transitions on demand.
CRIS-Team Scopus Importer:2024-11-01
Keywords: anisotropic excitons; fine structure; mid-infrared spectroscopy; ultrafast dynamics; van der Waals magnets

Waveguide optics in transition metal dichalcogenides visualized with near-field imaging - Mooshammer, Fabian; Xu, Xinyi; Trovatello, Chiara; Schuck, P. James; Basov, D. N. (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2024)
We advance the potential of transition metal dichalcogenides for integrated photonics by exploring near-infrared waveguide optics in 3R-MoS2. The interference patterns of waveguide modes in nano-optical near-field images allow us to quantify the anisotropic dielectric tensor, providing essential parameters for phase-matched optical devices. Using a custom laser-patterning routine, we write gratings into van der Waals (vdW) slabs. Their functionality is verified by two experimental findings: the directional outcoupling of different waveguide modes and grating-coupled waveguide second-harmonic generation. Our work demonstrates the feasibility of compact frequency converters and examines the tunings knobs that enable optimized coupling into layered waveguides.
CRIS-Team Scopus Importer:2024-11-01
Keywords: gratings; laser patterning; near-field; nonlinear optics; van der Waals materials; waveguide